Efek Reaksi Isomerisasi Pada Miristisin Terhadap Potensinya Sebagai Tabir Surya Secara in-vitro - Hery Muhamad Ansory; Ika Nur Fitriani (Fakultas Farmasi Universitas Setia Budi, 2021)
Myristicin has an alkenyl benzene structure with a double bond that is not conjugated with a benzene ring with good sunscreen activity, the change of the double bond to the conjugated position can be done by an isomerization reaction. This change will result in the molecule having longer delocalized double bonds and is expected to increase its activity as a sunscreen. The purpose of this study was to see the effect of changes in myristicin structure on its activity as a sunscreen. The isomerization reaction was carried out by reflux method using 20% ​​KOH catalyst in ethanol for 5 hours. Sunscreen activity test was carried out in-vitro using a UV spectrophotometer. The results of the isomerization reaction obtained isomyristicin in the form of a clear light yellow liquid that dissolves in ethanol (1: 1) with a% yield of 84% and a purity of 90% E: Z (6: 1). The results of the sunscreen activity test showed changes that were not much different between myristicin and isomyristicin, which indicated that the isomerization reaction had no significant effect on sunscreen activity.